Hit the road, Mac. - Ayers, Leslie
'Tis the season for summer travel, and we know you want to bring your gear with you while are on the road--or the plane, train, or boat. We share the best accessories, give you tips and tricks to stay connected, and show you how your iPhone may be the only computer you really need while you're on go.
Keywords: Macintosh (Computer); Laptop computers; Hard disks (Computer science); iPhone (Smartphone); Portable media players; Intenet; Mobile accessories; Electronic gadgets charger; Notebook Lock